Dampak Motivasi Investasi, Persepsi Resiko, Literasi dan Efikasi Keuangan Terhadap Minat Mahasiswa Berinvestasi Di Pasar Modal: Keywords: Investment Motivation; Risk Perception; Financial Literacy; Financial Efficacy; Investment Interest. - Wahyuningtyas, Endah Tri; Hasanah, Fuadatul; Susesti, Dina Anggraeni (Jurnal Akuntansi AKUNESA, 2022)
In an effort to grow the interest of student investment in the capital market. This research aims to find out the impact of investment motivation, risk perception, financial literacy and financial efficacy on students' interest in investing in capital markets. The study used primary data obtained from questionnaire results. The object in the study is an active student of Nahdlatul Ulama University Surabaya. The population of this study is 4.571 students. The sample selection technique used is Purposive Sampling so that it obtains a sample of 242 students who have attended seminars / training / investment courses or capital markets. This research uses a quantitative approach. The data was analyzed using SPSS version 25. The results of this study show that investment motivation and financial literacy have a positive impact while risk perception and financial efficacy have no impact on students' interest in investing in capital markets.